Reconciling the returns to education in off-farm wage employment in rural China - de Brauw, Alan; Rozelle, Scott (Wiley, 2008)
Previous studies have found that the returns to education in rural China are far lower than estimates for other developing economies. In this paper, we seek to determine why previous estimates are so low and provide estimates of what we believe are more accurate measures of the returns. Whereas estimates for the early 1990s average 2.3 percent, we find an average return of 6.4 percent. Furthermore, we find even higher returns among younger people, migrants, and for post‐primary education. The paper demonstrates that, although part of the difference between our estimate and previous estimates can be attributed to increasing returns during the 1990s, a larger part of the difference is due to the nature of the data and the methodological approaches used by other authors.